Profiling of bacterial community in a full-scale aerobic composting plant - Karadag, Dogan; Ozkaya, Bestami; Olmez, Esra; Nissila, Marika E.; Cakmakci, Mehmet; Yildiz, Senol; Puhakka, Jaakko A. (ELSEVIER SCI LTD, 2013)
Changes in temperature, pH, moisture, C/N ratio, and bacterial community were monitored in Istanbul full-scale composting plant. C/N ratio steadily decreased during composting and final mature compost products had a C/N ratio of less than 20. During the composting process, temperature was mostly above 55 degrees C and decreased to mesophilic conditions in the matured stages. Different types of bacteria were dominant in every stage of composting and bacterial diversity changed mainly by temperature. Bacillus species were dominant in early stages of composting while Acinetobacter and Sphingobacterium strains were detected in thermophilic and maturing stages. Bacteria were mainly active in the degradation of cellulose and toxic organics while some strains had denitrification ability. Generally, thermophilic stages were more rich in bacterial diversity than mesophilic and hyperthermophilic conditions significantly changed the bacterial community. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Aerobic; Full-scale composting; PCR-DGGE; Temperature; Microbial community; SP-NOV.; CONTAMINATED SOIL; CATTLE MANURE; BIOREMEDIATION; SUCCESSION; DIVERSITY; DYNAMICS; SEQUENCE; STRAINS; Biotechnology & Applied Microbiology; Environmental Sciences & Ecology